2018
DOI: 10.1186/s12879-018-2947-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial susceptibility testing of human Brucella melitensis isolates from Ulanqab of Inner Mongolia, China

Abstract: BackgroundBrucellosis is an endemic disease in the Inner Mongolia Autonomous Region of China and Ulanqab exhibits the highest prevalence of brucellosis in this region. Due to the complex nature of Brucellosis, a cure for this disease has proven to be elusive. Furthermore, the reduced susceptibility of Brucella spp. to antimicrobial agents has been reported as a potential cause of therapeutic failure. However, detailed in vitro antimicrobial susceptibility patterns pertaining to Brucella isolates from this regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 31 publications
3
19
1
Order By: Relevance
“…Hence, these findings are in agreement with previously published reports from Egypt that clearly showed an increase in antimicrobial resistance in various other human pathogens [37]. Reduced rifampicin susceptibilities in B. melitensis strains were also reported from Iran, Malaysia, China, and Kazakhstan [46,48,63,64,66].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Hence, these findings are in agreement with previously published reports from Egypt that clearly showed an increase in antimicrobial resistance in various other human pathogens [37]. Reduced rifampicin susceptibilities in B. melitensis strains were also reported from Iran, Malaysia, China, and Kazakhstan [46,48,63,64,66].…”
Section: Discussionsupporting
confidence: 92%
“…All B. melitensis and B. abortus isolates in this study were sensitive to chloramphenicol, gentamicin and tetracycline. These findings are comparable to previously published reports in Egypt, China, Qatar and Kazakhstan [46,48,65,66].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…is rpoB , and some results showed that variation in the rpoB gene caused reduced sensitivity to rifampicin [ 37 ]. The latest study showed that some Brucella isolates with no variations in rpoB are resistant to rifampicin [ 38 , 39 ]. In our study, no variations in rpoB of any rough B. melitensis strain were observed.…”
Section: Discussionmentioning
confidence: 99%